The relationship between smartphone overuse and sleep in younger children: a prospective cohort study - Kim, So Yeon (J Clin Sleep Med, 2020)
STUDY OBJECTIVES: Younger children and adolescents are exposed to various smart devices in the modern world, and their use of smart devices is rapidly increasing worldwide. Although smart devices have often been considered to have negative effects on sleep of children and adolescents, such effects have not been studied among younger children. Sleep is considered particularly important for learning and memory, and also has implications for emotional regulation and behavior. Therefore, this study was conducted to examine the effects of smartphone overuse on sleep in 5- to 8-year-old children. METHODS: Participants were from the Kids Cohort for Understanding of Internet Addiction Risk Factors in Early Childhood (K-CURE) Study, an observational prospective cohort study in Korea. Smartphone screen time and total sleep time were assessed using parental questionnaires. Sleep problems of children were assessed using the Children's Sleep Habits Questionnaire (CSHQ). Analysis of covariance was used to examine the association between smartphone overuse and sleep habits in children. All statistical analyses were conducted using SPSS version 21.0 (IBM Corporation, Armonk, NY). RESULTS: Total sleep time of the smartphone overuse group (smartphone use over 1 hour daily) was shorter than that of the control group (F = 6.362, P < .05). Children in the smartphone overuse group showed statistically significant higher scores in the CSHQ total score and nocturnal awakening subscale score (P < .05). CONCLUSIONS: Excessive smartphone use was related to shorter total sleep time in children. Use of a smartphone was also associated with significant reductions in the quality of sleep in younger children. CITATION: Kim SY, Han S, Park E-J, et al. The relationship between smartphone overuse and sleep in younger children: a prospective cohort study. J Clin Sleep Med. 2020;16(7):1133–1139.